2017
DOI: 10.1037/dev0000364
|View full text |Cite
|
Sign up to set email alerts
|

The link between perceived maternal and paternal autonomy support and adolescent well-being across three major educational transitions.

Abstract: To what extent does maternal and paternal autonomy support enhance well-being across the major transitions of high school? We tested the degree to which perceived autonomy supportive parenting facilitated positive changes in self-esteem and life satisfaction and buffered against negative changes in depressive symptoms and school related burnout in 3 Finnish longitudinal studies, each with a measurement point before and after a major transition (middle school, N1 = 760, 55.7% girls; high school, N2 = 214, 51.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
92
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 107 publications
9
92
1
5
Order By: Relevance
“… consistent, ongoing parental support (Smith et al , ; Waters et al , ) Stable home environment (Hammond, ) responsive and engaged parents (Hammond, ) parenting encourages (Duineveld et al , ) older sibling in secondary school (Mackenzie et al , ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… consistent, ongoing parental support (Smith et al , ; Waters et al , ) Stable home environment (Hammond, ) responsive and engaged parents (Hammond, ) parenting encourages (Duineveld et al , ) older sibling in secondary school (Mackenzie et al , ) …”
Section: Resultsmentioning
confidence: 99%
“…Research suggests that family relationships may bear more importance during transitions than in‐school relationships and other factors (Benner & Graham, ; Waters et al , ), such as consistent and ongoing support from parents (Smith, Akos, & Lim, ; Waters et al , ), stable home environment (Hammond, ), responsive and engaged parents (Hammond, ), brother/sister who is already studying in their new school (Mackenzie et al , ), and parenting which promotes the independence and autonomy of their child (Duineveld, Parker, Ryan, Ciarrochi, & Salmela‐Aro, ). Duineveld et al () reported that supporting autonomy had a positive influence on the child’s self‐esteem and, conversely, a negative impact on depressive symptoms during primary‒secondary transitions. Waters et al ’s () Australian study reported that pupils with a close relationship to their parents were more likely to have a relatively easy transition.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the home environment, they found that mothers provided greater autonomy support (i.e., supporting the child’s self-governance and control over their life; Keller, 2016) compared to fathers prior to the transition. Moreover, Duineveld et al (2017) reported greater levels of autonomy support before the transition significantly predicted a decline in depression after children moved to secondary education. This finding indicates that autonomous, supportive parenting that encourages independence may protect children from developing mental health disorders during the transition to secondary education.…”
Section: The Effects Of the Transition To Secondary Education On Emotmentioning
confidence: 96%
“…Duineveld et al (2017), who studied the secondary education transition in Finland, reported decreased depressive symptoms, decreased life satisfaction, and increased emotional exhaustion following the transition. In terms of the home environment, they found that mothers provided greater autonomy support (i.e., supporting the child’s self-governance and control over their life; Keller, 2016) compared to fathers prior to the transition.…”
Section: The Effects Of the Transition To Secondary Education On Emotmentioning
confidence: 99%
“…As a result, a significant number of investigations on doctoral education have fo-cused on finding ways to enhance doctorate students' persistence and engagement (e.g., Hoskins & Goldberg, 2005;Stubb, Pyhältö, & Lonka 2014Vekkaila et al, 2013. Among various predictors of students' persistence and engagement, the most common variable is motivation, which has been comprehensively investigated in a variety of educational contexts and has been consistently found associated with positive learning experiences (Orsini, Binnie, & Tricio, 2018), improved learning outcomes (Cerasoli & Ford, 2014), effort (Miller, Ramirez, & Murdock, 2017), engagement (Cheon, Reeve, & Song, 2016), student satisfaction (Wach, Karbach, Ruffing, Brünken, & Spinath, 2016) and enhanced well-being (Duineveld, Parker, Ryan, Ciarrochi, & Salmela-Aro, 2017). In-depth and focused studies exclusively on the role of motivation are not common in doctoral studies (Sverdlik, Hall, McAlpine, & Hubbard 2018), despite the critical role of motivation.…”
Section: Introductionmentioning
confidence: 99%